2022
DOI: 10.1101/2022.02.25.22271511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BA.2 evasion of vaccine induced binding and functional non-neutralizing antibodies

Abstract: The number of mutations in the omicron (B1.1.529) BA.1 variant of concern (VOC) led to an unprecedented evasion of vaccine induced immunity. However, despite the remarkable rise in global infections, severe disease and death did not increase proportionally, linked to persistent recognition of BA.1 by T cells and non-neutralizing opsonophagocytic antibodies. Yet, the emergence of a new sublineage, BA.2, that is more transmissible compared to BA.1, despite relatively preserved neutralizing antibody responses, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Evidence on neutralization data found a 20-fold reduction in neutralization associated with the Omicron variant [94] and lower neutralizing antibody titers to BA.1 and BA.2 when compared with wild-type SARS-CoV-2 [76,95]. Studies indicate similar humoral responses among BA.1 and BA.2 [76,95,96]. This evidence complements the epidemiological observation of higher rates of reinfection reported for Omicron compared with other virus variants [70].…”
Section: The Impact Of Variants Of Concern Globally and In The Apacsupporting
confidence: 67%
“…Evidence on neutralization data found a 20-fold reduction in neutralization associated with the Omicron variant [94] and lower neutralizing antibody titers to BA.1 and BA.2 when compared with wild-type SARS-CoV-2 [76,95]. Studies indicate similar humoral responses among BA.1 and BA.2 [76,95,96]. This evidence complements the epidemiological observation of higher rates of reinfection reported for Omicron compared with other virus variants [70].…”
Section: The Impact Of Variants Of Concern Globally and In The Apacsupporting
confidence: 67%
“…The BA.2 subvariant is becoming the predominant strain of SARS-CoV-2 by replacing the BA.1 subvariant with a higher transmissibility ( Chen and Wei, 2022 ). It is reported that BA.2 could potentially evade natural and vaccine-induced immunity, rather than BA.1 ( Bartsch et al., 2022 ). The discrepancies in transmissibility and pathogenicity between the BA.1 and BA.2 subvariants make it necessary to conduct differential diagnosis of the Omicron subvariants in COVID-19 patients ( Hamill et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%